Uterine rupture in a pregnancy without previous uterine scarring and induction of labor with misoprostol: a case report - Quintana Islas, Verónica; Cid Gómez, Olga; Díaz Aldeco Castillo, Christopher Díaz Aldeco Castillo; Noguera Echeverría, Alexis Emir; Ibarra Guerrero, María Fernanda; Barrera Heredia, Leonel Andrés; Tharlene Auguste, Guiscentia Rose; Ruz Alcocer, Alison Mariel; Gómez Marfil, Natalia Aleli; Dominguez de la Cruz, Ambar Sahian; Nava Rodríguez, Francisco Alejandro (International Journal of Research in Medical Sciences, 2025)
Uterine rupture (UR) is a serious obstetric complications involving the uterine wall injury during pregnancy or delivery. It occurs in one in 5,000 to 7,000 births, with about up to 10% requiring hysterectomy. Risk factors include previous uterine scarring, use of uterotonics, induction of labor, history of uterine trauma, high multiparity, abnormal placentation, fetal abnormalities, advanced maternal age, a high body mass index (BMI), and lack of prenatal monitoring. A 36-year-old Mexican female with five previous pregnancies, all terminated by vaginal route, with poor prenatal monitoring and high blood pressure. Prostaglandin E1 (misoprostol 50 mcg) was used in two doses with the patient starting labor in an active phase, but presented moderate abdominal pain, no fetal heart rate, and weak transvaginal bleeding. A probable detachment of placenta and fetal death was suspected; therefore, it was decided to perform an emergency caesarean section. This case highlights the importance of obstetric care, particularly in relation to gestational hypertension, induction of labor, and severe complications as uterine rupture. In our patient misoprostol was used to prepare the cervix and promote induction of term delivery, but its administration led to uterine rupture. UR is a rare obstetric emergency that requires immediate attention and proper surgical management. It is more common in women with previous uterine scarring and can occur in a uterus without a surgical history. Risk factors and clinical monitoring are crucial for early warning signs. Misoprostol use should be adjusted based on patient characteristics and pre-existing factors. Timely diagnosis and treatment are essential to reduce morbidity and mortality.